2015 Land cover map of Southeast Asia at 250 m spatial resolution. Issue 7 (2nd July 2016) - Miettinen, Jukka; Shi, Chenghua; Liew, Soo Chin
ABSTRACT: In this letter, we present the methodology and accuracy assessment results of a new 250 m spatial resolution land cover map of Southeast Asia (covering Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand, Timor-Leste and Vietnam). The map is based on semi-automated classification of Moderate Resolution Imaging Spectroradiometer data (acquired January to November 2015) supported by various auxiliary data sets. The classification scheme with 18 land cover classes reflects the characteristics of land cover in Southeast Asia and aims to provide useful input for various regional-level analyses requiring information on land cover distribution. The accuracy of the map is assessed separately for the seasonal (north of 9° N) and humid (south of 9° N) parts of the region, reaching 82% and 86% overall accuracies respectively. The map will be made available at:https://ormt-crisp.nus.edu.sg/ormt/Home/Disclaimer